Implementation of Sharia Value and Marketing on Customer Satisfaction in Local Sharia Development Bank of Jateng - Cahyani, Putri Dwi; Utami, Restu Frida (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2018)
Sharia Bank of Jateng, Puwokerto is a sharia unit that was established in 2014, has a big challenge to expand market share both from the competition of Islamic and conventional banking in Purwokerto city. Maximizing sharia marketing is expected to be the strength of Sharia Bank of Jateng which aims to provide customers satisfaction. There are four item in sharia marketing that become guidelines for sharia marketers, Rabbaniyyah (Theistic), Akhlāqiyyah (Ethic), Al-Waqī'iyyah (Realistic) and Insāniyyah (Humanism). In this study, it examines the effect of sharia marketing and how the influence of sharia marketing value characteristics towards customer satisfaction. This research was conducted by distributing questionnaires to 100 customers by using purposive sampling. To find out how far the independent variables can affect the dependent variable, we using multiple linear regression. Based on the results of regression analysis that theistic beta values are 0.399, ethical at 0.498, realistic at 0.561, and humanist at 0.262 to customer satisfaction. Variables that are very dominant affecting customer satisfaction is realistic variables. Testing the hypothesis, it is known that theistic, ethical, realistic and humanist have a positive effect on customer satisfaction in saving at Sharia Bank of Jateng, Purwokerto.